Aplikasi Zoom pada Pelatihan Kepemimpinan Administrator - Atpriatna Utama (Sustainable, 2020)
The pandemic forced all training activities to become disrupted, the way that is commonly done with zoom application technology. The purpose of this study is to provide an argument that occurs in an administrator leadership training in 2020 during a pandemic with a zoom facility. A descriptive qualitative method with questionnaires to participants with a google form, and analyzed with a google sheet, analyzing the results of interviews and participatory observation. Based on the results of the analysis, it is known that the zoom-in participants who are in the category x generation experiences boredom, and claims that the ideal zoom time of 1-3 hours is 69.7%. And as many as 31.3% claims to be more than 3 hours, with the zoom condition is not monotonous. The results of this study are only limited to the operational aspects of zoom, there are other possible aspects to provide better outcomes for Administrator Leadership Training.